C‐reactive protein, delirium, and other psychological symptoms among patients with advanced cancer. Issue 2 (7th June 2020) - Amano, Koji; Hatano, Yutaka; Matsuda, Yoshinobu; Maeda, Isseki; Ishiki, Hiroto; Miura, Tomofumi; Imai, Kengo; Hori, Tetsuo; Matsuda, Yosuke; Funaki, Hiromi; Suzuki, Kozue; Mori, Masanori; et al.
Abstract: Background: It remains unclear whether a relationship exists between elevated C‐reactive protein (CRP) levels and delirium. The primary aim was to investigate the relationship between CRP and delirium in advanced cancer. Methods: This study was a multicenter prospective cohort study conducted in palliative care units. At baseline, the physicians diagnosed delirium. On the seventh day, they evaluated whether new delirium had occurred. Subjects were divided into four groups according to CRP levels. We assessed the associations between CRP levels and proportions of delirium. To evaluate the relationship between CRP and delirium, adjusted odd ratios (ORs) and 95% confidence intervals (CIs) were calculated in the logistic models. Results: Among 1896 patients, 1354 patients were eligible for analyses. We classified them into four groups: low (CRP < 1 mg/dl) ( n  = 170), moderate (1 ≤ CRP < 5 mg/dl) ( n  = 453), high (5 ≤ CRP < 10 mg/dl) ( n  = 334), and very high (10 mg/dl ≤ CRP) ( n  = 397). The incidence of delirium significantly increased with increasing CRP levels ( P  = 0.02). In model 1, significantly higher adjusted ORs than in the low CRP group were observed in the high CRP and very high CRP groups (1.63 [95% CI 1.06–2.50], P  = 0.03; 1.72 [95% CI 1.13–2.62], P  = 0.01, respectively). In model 2, a significantly higher adjusted OR than in the low CRP group was observed in the very high CRP group (1.61 [95% CI 1.05–2.45], P  = 0.03). Conclusions: Relationships existed between elevated CRP levels and delirium.